Catalytic β-Bromohydroxylation of Natural Terpenes: Useful Intermediates for the Synthesis of Terpenic Epoxides - Saadia Oubaassine; Angela Köckritz; Reinhard Eckelt; Andreas Martin; Mustapha Ait Ali; Larbi El Firdoussi (Journal of Chemistry)
In a one-step procedure, various β-bromoalcohols were synthesized from natural terpenes in good to excellent yields. Using different catalysts, the reaction was carried out at room temperature, with H2O as nucleophile and N-bromosuccinimide as a bromine source under mild reaction conditions. The synthesized β-bromoalcohols were subsequently converted in situ to the corresponding epoxides in good yields.